2002
DOI: 10.1590/s0100-29452002000100034
|View full text |Cite
|
Sign up to set email alerts
|

Porta-enxertos para a lima-ácida-'Tahiti' na região de Bebedouro, SP

Abstract: Foi instalado um experimento de seleção de porta-enxertos para a lima-ácida-'Tahiti' (Citrus latifolia Tanaka), em dezembro de 1988, na Estação Experimental de Citricultura de Bebedouro-SP, com o objetivo de conhecer seu comportamento e oferecer novas opções de plantio para as condições ecológicas semelhantes às daquela região. A variedade copa, originária do BAG-Citros do IAC, localizado no Centro de Citricultura Sylvio Moreira, Cordeirópolis-SP, é um clone nucelar de 'Tahiti', denominado IAC-5. Os porta-enxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
27

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 1 publication
1
10
0
27
Order By: Relevance
“…The trifoliate orange, 'Sunki' mandarin, and 'Cleopatra' mandarin did not show differences among themselves and presented the smallest plant development values. In similar studies with rootstocks for 'Tahiti' lime, trees with great vigor were obtained on 'African' rough lemon (Foguet et al, 1994), 'Volkamer' lemon (Valbuena, 1994), and 'Troyer' and 'Carrizo' citranges (Grisoni et al, 1989). Donadio et al (1993) reported that 'Tahiti' lime trees of the 'IAC-5' clone had low vigor when budded on 'Cleopatra' mandarin.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The trifoliate orange, 'Sunki' mandarin, and 'Cleopatra' mandarin did not show differences among themselves and presented the smallest plant development values. In similar studies with rootstocks for 'Tahiti' lime, trees with great vigor were obtained on 'African' rough lemon (Foguet et al, 1994), 'Volkamer' lemon (Valbuena, 1994), and 'Troyer' and 'Carrizo' citranges (Grisoni et al, 1989). Donadio et al (1993) reported that 'Tahiti' lime trees of the 'IAC-5' clone had low vigor when budded on 'Cleopatra' mandarin.…”
Section: Resultsmentioning
confidence: 92%
“…Some studies conducted in the State of São Paulo indicated as alternative rootstocks to 'Rangpur' lime for 'IAC-5': 'EEL' trifoliate orange, 'Swingle' citrumelo, 'Orlando' tangelo, 'Morton' citrange, and 'Volkamer' lemon (Figueiredo et al, 2000;2002). However, the behavior of rootstocks may vary depending on soil type, climate, diseases, and cropping practices.…”
Section: Introductionmentioning
confidence: 99%
“…In the initial growth phase, 'Carrizo' citrange, 'Rangpur' lime, 'Swingle' citrumelo and 'troyer' citrange, induced greater growth in canopy volume in 'tahiti' acid lime (TABLE 1) In studies conducted by Figueiredo et al (2002), in Bebedouro-SP, the authors found that 'volkameriano' 'Catania 2' lemon and 'Orlando' tangelo promoted greater development of the 'tahiti' canopy, with maximum value of 123.83 m 3 of average canopy volume in plants with nine years of age, and most values were close to those reported in this work in plants still at seven years of age. It is important the selection of rootstocks that induce the formation of smaller canopies, with high productive efficiency in relation to their volume, so as to allow the formation of more dense plants and to obtain greater production by area (SaNtOS et al, 2015) .…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, there are few researches carried out with this objective. Figueiredo et al (2002), working with ten alternative rootstocks to 'Rangpur' lime tree in the region of Bebedouro, recommended 'Orlando' tangelo, 'morton' citrange, 'Swingle' citrume, 'volkameriano' lime and 'limeira' trifoliate. On the other hand, Stenzel and Neves (2004) observed that 'tahiti' plants grafted on 'Rangpur' lime and 'C-13' citrange presented the highest accumulated yields.…”
Section: Introductionmentioning
confidence: 99%
“…1). O clima, segundo Figueiredo et al (2002), utilizando a classificação de climática de Köppen, é do tipo Cwa (subtropical com inverno moderado e seco, verão quente e chuvoso), com temperatura média máxima de 28,8ºC, média mínima 18,3ºC e temperatura média de 23,5ºC. A precipitação média anual é de cerca de 1.400 mm.…”
Section: Introductionunclassified